A crystalline AlPO4-5 intermediate: designed synthesis, structure, and phase transformation. Issue 36 (6th September 2017) - Lin, Cong; Li, Jian; Pan, Fengjuan; Zhao, Yifang; Xu, Le; Yang, Yanquan; Du, Xin; Lin, Xiaohuan; Liao, Fuhui; Lin, Jianhua; Yang, Tao; Sun, Junliang
Abstract : A crystalline AlPO4-5 intermediate with phase transformability is designedly synthesized, providing new thoughts for the crystallization mechanism studies. Abstract : AlPO4 -5 is the most extensively studied material in exploring the crystallization mechanism of aluminophosphate molecular sieves, and it can be synthesized using 4-dimethylaminopyridine (DMAP) as an organic structure-directing agent (OSDA). Achieving the AlPO4 -5 intermediate in the crystalline form would be of great importance and significance for this purpose. In this study, we proposed a concept that by carefully regulating the synthesis conditions, crystalline alumimophosphate intermediates could be rationally prepared. A crystalline AlPO4 -5 intermediate, (C7 H11 N2 )2 (H3 O)(Al3 P4 O16 )·(H2 O)2.5 (1 ), was, therefore, synthesized by significantly increasing the amounts of orthophosphoric acid and DMAP. The intermediate1 consists of alternating organic DMAP and inorganic [Al3 P4 O16 ] 3− layers with abundant hydrogen bonds and can transform to the AlPO4 -5 framework upon heating in air or through a steam-assisted conversion (SAC) method. To unravel the role of DMAP in the transformation, pure AlPO4 -5 (2 ) was also synthesized by altering the synthesis conditions. The supramolecular assembly templating (SAT) effects of DMAP in1 and2 were verified via fluorescence spectra. Thus, the π–π stacking interactions between the DMAP molecules and the abundant hydrogen bonds between the adjacent layers are considered to be important for the phase transformation of1 . This crystalline intermediate would promote the understanding of the crystallization mechanism in the system of aluminophosphate molecular sieves.